Relevansi Ayat-ayat Edukatif dalam Pengembangan Kurikulum Pendidikan Islam di Indonesia - Umiarso, Dina Mardiana (Edukasia Islamika : Jurnal Pendidikan Islam, 2018)
The thought of ideal curriculum development in Indonesia keeps on scrolling. It wasstarted from curriculum 1947, 1949, 1952, 1964, 1968, 1975, 1984, 1994, Competencebased Curriculum (KBK), School-based Curriculum (KTSP), and the 2013 Curriculum.Those changes are the answers of global demand to the education quality. However, bylooking at the fact that there are many cases of students fight, drug abuse and free sexamong students, it can be concluded that the curriculum changes are not in line with thereality in education world. Based on the explanation above, this paper tries to offer an idea to develop curriculum based Qur’an by reviewing one of the term used in Qur’an torefer to the educational process, namely: ‘ta’lim’. Based on the analysis, the word ta’limhas a deep meaning including cognitive, affective, and psychomotor domains. If it isrelated to the curriculum development, curriculum based Qur’an is a learning modelwhich focuses on the three domains above, as seen on the meaning coverage of ta’limused in Qur’an.